Exploring laboratory operations: a comprehensive guide / Norhayati Mohd Zain - Mohd Zain, Norhayati (Faculty of Pharmacy, 2023)
Modul Kenali Makmal Anda (MoKMA23) was held on 11 October 2023 at MPG 1 - 6 involving 213 semester one and 175 semester five pharmacy students. The main purpose of this module was to expose students to laboratory regulations, health, and safety such as general laboratory safety, disposal and waste material, how to handle material and chemicals, emergency equipment and safety tools, and personal protection equipment (PPE).